Study on Design and Analysis of Industrial Y Type Strainer. Issue 1 (March 2021) - Patel, Mohammed Ather; Saheb, Shaik Himam
Abstract: Industrial Strainers are widely being used in Various Heavy Mechanical Industries such as Petro Chemical, Oil and Gas, Steel industry, Water Treatment and Process Industries. The Main purpose being Removal of unwanted Materials in pipelines is a never ending one. Whether the Flowing Material as Sea Water, Oil, Paint or variety of Food or Chemical products. The cause of damage might be dirt, foreign matter or even Clamps of the Product. The Main widely used Industrial Strainers are Basket, Magnetic, Duplex, Y-Type, Tee type and conical strainer. The material used in overall Manufacturing of the Different Strainers is MS (Mild Steel), SS (Stainless Steel). The most efficient of all the strainers Duplex Strainer, because of its large design ratio and larger Material Handling Capacity. The Main Purpose of this Research is to Study Design and Materials involved in the manufacturing of Y-Type are being mainly used in the fluid pipelines in order to Filter Out the impurities, Foreign Particles and protect the downstream.